2018
DOI: 10.4103/jphi.jphi_5_19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotics in the treatment of acute noninflammatory diarrhea in hospitalized children aged 2–10 years

Abstract: Objective: Diarrhea is the second leading cause of death in children. Therefore, the aim of this study was to investigate the effect of probiotics in the treatment of acute noninflammatory diarrhea in children aged 2-10 years in the Pediatric Ward of Hajar Hospital in Shahrekord. Methods: This clinical trial was performed on 184 children with diarrhea. Eighty-six children were randomly assigned to the KidiLact probiotic group and 87 ones to the control group. Patients' demographic information, symptoms, and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Detailed characteristics of the included RCTs are presented in Table S2 , and excluded trials are shown in Table S3 . Ultimately, 15 RCTs that randomized 1765 participants (895 in the experimental group and 870 in the control group) were included [ 10 , 11 , 12 , 16 , 17 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed characteristics of the included RCTs are presented in Table S2 , and excluded trials are shown in Table S3 . Ultimately, 15 RCTs that randomized 1765 participants (895 in the experimental group and 870 in the control group) were included [ 10 , 11 , 12 , 16 , 17 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, caution is needed when interpreting these results, as two included studies [ 20 , 22 ] did not report the dose of each probiotic strain in the intervention; besides this dose issue, the course of acute gastroenteritis could also affect the efficacy of the probiotic. We think this is the most comprehensive analysis of this probiotic strain that has been conducted to date, and we hope that our findings will be especially useful to decision-makers.…”
Section: Discussionmentioning
confidence: 99%
“…Bakteri yang digunakan yaitu Lactobacillus casei, Lactobacillus acidophilus, Lactobacillus rhamnosus, Lactobacillus bulgaricus, B.infantis, Bifidobacterium brevis, dan Streptococcus thermophilus. Rerata frekuensi diare pada hari ke-2 dan ke-4 ,durasi demam, durasi diare, dan lama rawat inap secara signifikan lebih rendah pada kelompok probiotik (Khoshdel et al, 2018). Dosis probiotik yang digunakan adalah 2 kali sehari ½ sachet untuk usia 0-6 bulan dan 2 kali sehari 1 sachet untuk usia diatas 6 bulan.…”
Section: Kombinasi Multi Bakteri Probiotikunclassified